A contribution to the study of a relationship fluorine-manganese in rats - Oliveira, Ida Maria Vianna de; Pourchet-Campos, Maria Apparecida (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
An experiment to determine the effects of varying the manganese concentration of the diet on the fluorine retention in the femur of rats was made. Four groups of weaning rats were fed "ad libitum a 27% casein synthetic diet and were provided with water as follows: 1) distilled (control); 2) containing 1 ppm of fluorine (F); 3) 1,0 ppm F + 0,5 ppm Mn; 4) 1 ppm F + 1 ppm Mn. The weight gain and food and water consumption were measured during 60 days. The results indicated that manganese does not seem to affect the proportional fixation of fluorine in the femur. The authors think that more data should be available before a definite conclusion on the influence of the ratio F:Mn on the fluorine retention could be drawn.